PEMBERDAYAAN MASYARAKAT DALAM MEMANFAATKAN LIMBAH PRODUKSI TUNA LOIN MENJADI PRODUK EKONOMIS - Nur, Rinto M; Sibua, Nurhikma; Pahana, Andrha S; Mahamude, Safira Hari Yanti; Muhammad, Meyisyin Hi; Pina, Wihan; Alting, Nadia Muhammad; Seng, Meysi Riska; Kasim, Alkadri M; Seng, Uldin Sahdan (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity involves PKK mothers from Sangowo Village as partners. They face the problem of a lack of knowledge regarding the processing of by-products of fisheries into goods that have economic value. Therefore, the purpose of this activity is to provide socialization, training, and assistance to improve the understanding and skills of the community in processing fishery products. This activity was carried out in Sangowo Village between July and September 2024. This PKM activity includes several stages, such as surveys and preparation, socialization of the PKM program, and training in using tools and processing of tuna loin waste. The products taught to partners include nuggets, meatballs, and sticks. The results of implementing the PKM activity show how beneficial it is for the Sangowo Village community. Partners received the material presented by the PKM team well and participated in the training with enthusiasm and seriousness. The active involvement of partners in the product manufacturing process and the provision of recipe books also contributed to the success of this training. Thus, this activity succeeded in increasing the knowledge and skills of the local community in processing fishery products, demonstrating the effectiveness of the training